Evaluasi Program Pelatihan Komputer di LPK Teknos Ciruas Serang Banten - Hildayanti, Dyah; Permatasari, Rina; Sudrajat, Indra (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2023)
AbstractJob Training Institute (LPK) is an institution that aims to improve a life skill and is still in a non-formal education unit. According to Munthe 2015: 1, Program Evaluation is here to provide input, study and consideration in determining whether the program is worth continuing or stopping. The term makes program evaluation conditions commonplace in a non-formal and formal educational institution, including in training institutions and courses. In this context we use a descriptive study method with a qualitative approach. We evaluated the computer training program at LPK Teknoss Ciruas. The evaluation model used is the Contex-Input-Product (CPP) evaluation model. From the perspective of the learning process, no computer material or curriculum is developed in the rotation of batches per year. This means that the knowledge received by trainees is always the same in every generation or period and is not evolutionary. The implementation of Computer Training at LPK Teknoss Ciruas is based on the needs of students who have the motivation to learn to know computers to become proficient in both workers and students. So that the target and even the purpose of the computer training program at LPK Teknoss are in accordance with the needs of the training participants and the targets are in accordance with what is set. Supporting materials have also been carried out so that they are in accordance with the ideal standards of the curriculum. Media and learning tools consist of Modules, internet, and Computers. The computer training program at LPK Teknoss has achievement indicators that can be used as a benchmark for the success of training. Along with the development of the times, the needs in the world of work increasingly require us to have a skill. That's why there are currently many training programs that provide various programs to help improve skills.Key Words: Non Formal Education, CPP Evaluation, LPK Teknoss CiruasAbstrakLembaga Pelatihan Kerja (LPK) merupakan suatu lembaga yang bertujuan untuk meningkatkan suatu keterampilan hidup dan masih berada dalam satuan pendidikan non formal. Menurut Munthe 2015:1, Evaluasi Program hadir untuk memberikan masukan, kajian dan pertimbangan dalam menentukan apakah program layak untuk diteruskan atau dihentikan. Istilah tersebut membuat kondisi evaluasi program menjadi sesuatu yang lumrah di suatu Lembaga Pendidikan nonformal dan formal Tak terkecuali di Lembaga pelatihan dan kursus. Dalam konteks ini kami menggunakan metode studi descriptive dengan pendekatan kualitatif. Kami melakukan evaluasi pada program pelatihan komputer di LPK Teknoss Ciruas. Model evalusi yang digunakan adalah model evaluasi Contex-Input-Product (CPP). Dari perspektif proses pembelajaran, tidak ada materi atau kurikulum komputer yang dikembangkan dalam pergantian angkatan per tahunnya. Artinya pengetahuan yang diterima peserta pelatihan selalu sama pada setiap generasi atau periode dan bukan merupakan evolusi. Penyelenggaran Pelatihan Komputer di LPK Teknoss Ciruas didasarkan pada kebutuhan peserta didik yang memiliki motivasi ingin belajar mengenal computer hingga mahir baik pekerja maupun siswa. Sehingga sasaran bahkan tujuan dari adanya program pelatihan komputer di LPK Teknoss sudah sesuai dengan kebutuhan peserta pelatihan dan sasarannya pun sudah sesuai dengan yang ditetapkan. Materi penunjang pun sudah dilakukan sehingga sesuai dengan standar ideal kurikulum. Media dan alat belajar terdiri dari Modul, internet, dan Komputer. Program pelatihan komputer  di LPK Teknoss memiliki indikator ketercapaian yang bisa dijadikan sebagai tolak ukur keberhasilan dari pelatihan. Seiring berkembangnya zaman kebutuhan didunia kerja semakin menuntut kita untuk memiliki sebuah keterampilan. Karena hal itulah saat ini banyak sekali program pelatihan-pelatihan yang menyediakan berbagai program untuk membantu meningkatkan skills.Kata Kunci: Pendidikan Non Formal, Evaluasi CPP, LPK Teknoss Ciruas.